Development framework of work stress and technology absorptive capacity relationship among small and medium-sized enterprises (SMEs) in construction industry - Sallehuddin, Aina Mardia (2022)
The urges of technology adoption and usage raised work stress level within construction workforces. Construction industry is known as the slow technology growths industry and SMEs faced difficulties in technology adoption. Thus, such issues lead to high work stress and low level of technology absorptive capacity (TACAP) in the construction industry. Both work stress and TACAP is related to technology adoption, but no previous study explores work stress and TACAP in the same research area. Hence this research would like to explore work stress and TACAP scenario among SMEs in construction projects. This research is quantitative oriented, and questionnaire was the data instrument. This research was conducted among SMEs owner from G3 and G5 contractors within, Penang, Selangor, Pahang, and Johor with 196 respondents involved and 56% respondent rate. Descriptive statistical analysis and linear regression by using Statistical Package for Social Science (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM) by Smart PLS 3.0 used for data analysis. The findings showed there are 5 barriers rated as major barriers faced by SMEs in technology adoption; financial issue, human capital, incompetent management, limited external relationship and policy and procedure. The SMEs in the construction industry reported experiencing a moderate level of work stress and having a high level of TACAP by using non-R&D TACAP measurements. The relationship between work stress and TACAP also shows a positive connection. The proposed research framework was constructed based on the research finding and validated by 15 professionals. The proposed research framework aims to guide for SMEs to improve TACAP and technology adoption for the future.